Strengthening Economic Civic in Forming Independence of Santri as the Good Governance (Case Study of Al-Ittifaq Islamic Boarding School, Rancabali, Bandung) - Zulkifli; Nurdiana; Muchsin (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Development of pesantren role in empowering the community is one of the important efforts to strengthen the role of people in development because the government still faces a variety of cultural and structural problems, as well as the private sector tends to deviate to gain unilateral advantages. In exercising their development, empowerment is an approach that is relevant to strengthen the role of the community (civil society). The research objective was to analyze (1) the values instilled in the process of establishing the independence of the students through economy civic, (2) conceptual model and praxis of strengthening economy civic in establishing the independence of students as a form of good governance, (3) the factors strengthening economy civic in establish independence of students as a form of good governance. This study used a qualitative approach with case study method. Data collected through interviews, observation, documentation studies and literature studies. Subjects of research include builder boarding schools, boarding schools administrators, and students. Qualitative data analysis consists of three activities, namely data reduction, a data display, and conclusion drawing / verification. The results showed some things (1) the values of self-reliance of students of pesantren Al-Ittifaq is highlight the work ethic, high discipline, and ready for hard work, (2) conceptual model in establishing the independence of students with learning system AKOSA (naturally, pointed out, though, and apply). Praxis in forming the independence of the students through the formation of the core committee of agribusiness, doing practical training, forming Agribusiness Incubator Center (PIA), cooperation / partnership, and formed working groups agribusiness. As a manifestation of good governance pesantren Al-Ittifaq role as the private sector to foster public economic activities around the village of Natural Endah through cooperative Al-Ittifaq, while as civil society has been able to interact actively with various activities such as religious, economic, educational, social, and political. (3) The internal factors strengthening economic civic been producing products ranging from production (vegetables and livestock), packing, and marketing and external factors natural conditions Desa Alam Endah fertile, has been establishment of cooperation with farmers' groups, government agencies (Ministry of Commerce, Ministry of Agriculture, Ministry of Cooperatives and SMEs, and the Ministry of Social Affairs), educational institutions, businesses (Yogya Group, Toserba Banjaran, Kopo Mall).